Bentuk Implementasi Klasifikasi Periodontitis menurut American Academy of Periodontology 2018 Pada Berbagai Negara di Dunia - Farah Az Zahra, Elviena; Astuti, Luki; Christin Maitimu, Fergy (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Periodontal disease is a common dental health problem that can cause damage to the supporting tissues of the teeth. The classification of periodontal disease has continued to evolve, with the American Academy of Periodontology (AAP) releasing a new classification system in 2018. This system introduces the concepts of staging and grading to assess the severity and risk of disease progression. The implementation of this classification varies across countries, depending on resource availability and healthcare facilities. In developed countries, the adoption of this classification is faster due to technological support and integration into educational curricula, while developing countries still face significant challenges.